Biological effects of human placental extracts - variations in manufacturing methods and compositions - Alimu, Yikelamu; Yamamoto, Takeshi; Nakahata, Yasukazu (Frontiers in Pharmacology, 2025)
Placental extracts have been used in traditional medicine across many cultures for centuries. In Traditional Chinese Medicine and Japanese Kampo, placenta has been valued for its ability to reduce fatigue, promote recovery, and enhance vitality. This stems from the belief that the placenta possesses regenerative and life-sustaining properties. In the modern era, the therapeutic use of placenta began with Filatov’s “tissue therapy” in the Soviet Union, leading to the development of various extraction techniques from both human and animal placentas. Today, a variety of placental extracts has been manufactured using placentas from humans and livestock. The placental extracts that are currently being manufactured have different compositions owing to differences in origin, placental part used, and manufacturing methods. Despite the differences in the contents of these placental extracts, it has been shown that they exert, to some degree, common biological activities, such as antioxidant, anti-inflammatory, and immunomodulatory functions. Therefore, placental extracts are used as pharmaceuticals to treat menopausal disorders, improve liver function, treat osteoarthritis, and promote wound healing. They are also used as dietary supplements to improve skin texture and for anti-aging purposes. Notably, the relationship between the biological effects of a placental extract and its contents has not been accurately and comprehensively understood. This review summarizes the biological effects and functions of various placental extracts that have been reported to date, including our recent findings, and provides an overview of the biological effects of some human placental extracts for which we were able to obtain the manufacturing method information.